PERAN BUKU CERITA POP UP DALAM MENDUKUNG PERKEMBANGAN BAHASA DAN IMAJINASI ANAK - Herli Arma Dela; Desti Nirmala; Wulan Andriani Syafitri; Suci Ramadhani; Sabilla Husna (CV. Denasya Smart Publisher, 2026)
This paper aims to explain how pop-up storybooks can support the development of language and imagination in early childhood. Its main focus is to understand how the three-dimensional visual elements in pop-up books attract children’s attention and influence their ability to comprehend stories and express ideas. The method used is a literature study by reviewing various sources that discuss the use of visual media in children’s reading activities. The results show that pop-up books can increase children’s interest in stories, enrich vocabulary, and help them recognize the storyline more clearly. In addition, the interactive visual elements provide a more vivid imaginative experience, allowing children to respond to the story more creatively. The impact of using pop-up books can be seen in children’s growing confidence in speaking, storytelling, and expressing simple opinions. Therefore, pop-up storybooks can serve as an effective medium to support the development of language and imagination in early childhood learning activities.